The percentage of macrophage numbers in rat model of sciatic nerve crush injury - Satrio Wicaksono; Muhammad Ghufron; Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACTExcessive accumulation of macrophages in sciatic nerve fascicles inhibits regeneration of peripheral nerves. The aim of this study is to determine the percentage of the macrophages inside and outside of the fascicles at the proximal, at the site of injury and at the distal segment of rat model of sciatic nerve crush injury. Thirty male 3 months age Wistar rats of 200-230 g were divided into sham-operation group and crush injury group. Termination was performed on day 3, 7, and 14 after crush injury. Immunohistochemical examination was done using anti CD68 antibody. Counting of immunopositive and immunonegative cells was done on three representative fields for extrafascicular and intrafascicular area of proximal, injury and distal segments. The data was presented as percentage of immunopositive cells. The percentage of the macrophages was significantly increased in crush injury group compared to the sham-operated group in all segments of the peripheral nerves. While the percentage of macrophages outside fascicle in all segments of sciatic nerve and within the fascicle in the proximal segment reached its peak on day 3, the percentage of macrophages within the fascicles at the site of injury and distal segments reached the peak later at day 7. In conclusions, accumulation of macrophages outside the nerve fascicles occurs at the beginning of the injury, and then followed later by the accumulation of macrophages within nerve fascicles